The Art of the Impossible: Dave Barrett and the NDP in Power, 1972-1975 - Homel, Gene (Labour / Le Travail, 2014)
The article reviews the book, "The Art of the Impossible: Dave Barrett and the NDP in Power, 1972-1975," by Geoff Meggs and Rod Mickleburgh.
Keywords: ART of the Impossible: Dave Barrett & the NDP in Power 1972-1975; The (Book); BRITISH Columbia – Politics & government – 20th century; MEGGS; Geoff; MICKLEBURGH; Rod; NEW Democratic Party (Political party : British Columbia) – History – 20th century; Nonfiction